2021
DOI: 10.1021/acsbiomaterials.1c00733
|View full text |Cite
|
Sign up to set email alerts
|

Porous Inorganic Materials for Bioanalysis and Diagnostic Applications

Abstract: Porous inorganic materials play an important role in adsorbing targeted analytes and supporting efficient reactions in analytical science. The detection performance relies on the structural properties of porous materials, considering the tunable pore size, shape, connectivity, etc. Herein, we first clarify the enhancement mechanisms of porous materials for bioanalysis, concerning the detection sensitivity and selectivity. The diagnostic applications of porous material-assisted platforms by coupling with variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 186 publications
0
23
0
Order By: Relevance
“…The development of efficient, robust, and less toxic porous materials has been gaining tremendous attention for sustainable and effective utilization of CO 2 into value‐added fuels and chemicals. Silica‐based porous materials, such as MCM‐41, SBA‐15, and mesoporous silica, have set up important space in many emerging fields, including sensing, separation, catalysis, energy harvesting and storage, CO 2 capture and cycloaddition, drug delivery, biomedical field, water and air treatment, and coating [24–28] . The usage of silica‐based materials is mainly due to their porous structure and high surface area, which allow guest molecules to disperse or bind onto their internal pore [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of efficient, robust, and less toxic porous materials has been gaining tremendous attention for sustainable and effective utilization of CO 2 into value‐added fuels and chemicals. Silica‐based porous materials, such as MCM‐41, SBA‐15, and mesoporous silica, have set up important space in many emerging fields, including sensing, separation, catalysis, energy harvesting and storage, CO 2 capture and cycloaddition, drug delivery, biomedical field, water and air treatment, and coating [24–28] . The usage of silica‐based materials is mainly due to their porous structure and high surface area, which allow guest molecules to disperse or bind onto their internal pore [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Silica-based porous materials, such as MCM-41, SBA-15, and mesoporous silica, have set up important space in many emerging fields, including sensing, separation, catalysis, energy harvesting and storage, CO 2 capture and cycloaddition, drug delivery, biomedical field, water and air treatment, and coating. [24][25][26][27][28] The usage of silica-based materials is mainly due to their porous structure and high surface area, which allow guest molecules to disperse or bind onto their internal pore. [5] Polshettiwar et al synthesized a low-density three-dimensional dendritic fibrous nanosilica (DFNS) with superior structural features.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the application of this fast-growing research field has been considerably extended in areas ranging from medical diagnosis to energy storage. 4,5 Based on the dimensions of their pores, porous materials are classified by IUPAC as: microporous: pore size below 2.0 nm, mesoporous: between 2.0 to 50 nm and macroporous: pore dimensions above 50 nm. The performance of a porous material towards a particular application depends directly on its shape, size and void space.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, a review from Liu et al provided a complete overview of the inorganic porous nanomaterials and their use in bioanalysis and diagnostic. 8 They identified that various porous nanomaterials have been used in this field for three main purposes: (1) sample enrichment, (2) enzyme/ catalyst confinement, and (3) signal amplification. The review then covered various types of electrochemical-, optical-, and mass-spectroscopy-based sensors that have utilized porous materials for one of the three aforementioned purposes.…”
mentioning
confidence: 99%
“…In addition to therapeutics delivery, porous nanomaterials have gained tremendous attention for use in diagnostics and bioanalysis. In this direction, a review from Liu et al provided a complete overview of the inorganic porous nanomaterials and their use in bioanalysis and diagnostic . They identified that various porous nanomaterials have been used in this field for three main purposes: (1) sample enrichment, (2) enzyme/catalyst confinement, and (3) signal amplification.…”
mentioning
confidence: 99%